EVALUATION OF FACULTY MEMBERS' PERCEPTIONS OF SELF-EFFICACY AND UTILITY OF DISTANCE EDUCATION: AN EMPIRICAL STUDY ON FACULTY MEMBERS OF FACULTY OF ECONOMICS AND ADMINISTRATIVE SCIENCES OF FIRAT UNIVERSITY - Korkutan, Mümtaz; Uzun, Hasan (Fırat University, 2024)
Distance education systems have become an increasingly accessible and indispensable tool in education due to the rapid development and diffusion of communication technologies, changing individual characteristics, needs and demands. The increasing popularity of distance education programs requires a detailed analysis of their actual success and the factors that contribute to this success. The purpose of this study is to determine faculty members' distance education self-efficacy and perceptions of its utility. In this context, the relationship between self-efficacy perceptions and benefit perceptions and whether there is a statistical difference between the participants' perceptions and socio-demographic characteristics are also among the objectives of the study. While the population of the research consists of the faculty members of Fırat University Faculty of Economics and Administrative Sciences, the sample consists of 33 faculty members who voluntarily accepted to participate in the research, which covers 75% of the population. In the study, “Self-Efficacy Perception Scale for Distance Education” and “Perception of Benefit Scale for Distance Education” were used in accordance with the purpose of the research. Descriptive analyses (frequency, percentage, etc.), independent sample t-test and ANOVA analyses were used to test the research hypotheses. In ANOVA analysis, Tukey HSD test was applied to determine the difference between groups. As a result of the analyses, it was determined that faculty members' distance education self-efficacy perception levels were high, while their perception levels of usefulness were at a medium level. In addition, it was determined that distance education self-efficacy perception did not show a statistically significant difference according to the socio-demographic characteristics of the faculty members, but distance education benefit perception partially differed according to these characteristics. Finally, according to the correlation analysis, it was concluded that there was no relationship between faculty members' perceptions of self-efficacy in distance education and their perceptions of benefit. These findings suggest that faculty members' training needs and support mechanisms should be reviewed for the adoption and effective use of distance education.

Uzaktan eğitim sistemleri, iletişim teknolojilerinin hızlı gelişimi ve yaygınlaşması, bireysel özelliklerin, ihtiyaçların ve taleplerin değişmesi nedeniyle eğitimde giderek daha erişilebilir ve vazgeçilmez bir araç haline gelmiştir. Uzaktan eğitim programlarının artan popülaritesi, bu programların gerçek başarılarını ve bu başarıya katkıda bulunan faktörlerin ayrıntılı analizini gerektirmektedir. Bu çalışmanın amacı, öğretim üyelerinin uzaktan eğitim öz yeterlikleri ve kullanım yarar algılarını belirlemektir. Bu kapsamda öz yeterlik algıları ile yarar algıları arasındaki ilişki durumu ve katılımcıların algıları ile sosyo-demografik özellikleri arasında istatistiksel anlamda bir farklılaşma olup olmadığı da araştırmanın amaçları arasında yer almaktadır. Araştırmanın evreni Fırat Üniversitesi İktisadi ve İdari Bilimler Fakültesi öğretim üyelerinden oluşurken, örneklemi ise gönüllü olarak araştırmaya katılmayı kabul eden 33 öğretim üyesidir, bu da evrenin %75'ini kapsamaktadır. Çalışmada, araştırmanın amacına uygun olarak "Uzaktan Eğitime Yönelik Öz Yeterlik Algısı Ölçeği" ve "Uzaktan Eğitime Yönelik Yarar Algısı Ölçeği" kullanılmıştır. Araştırma hipotezlerinin test edilmesinde tanımlayıcı analizler (frekans, yüzde, vb.), bağımsız örneklem t-testi ve ANOVA analizlerinden yararlanılmıştır. ANOVA analizinde gruplar arasındaki farklılığı belirlemek amacıyla Tukey HSD testi uygulanmıştır. Yapılan analizler sonucunda, öğretim üyelerinin uzaktan eğitim öz yeterlik algı düzeylerinin yüksek, yarar algı düzeylerinin ise orta seviyede olduğu tespit edilmiştir. Ayrıca, uzaktan eğitim öz yeterlik algısının öğretim üyelerinin sosyo-demografik özelliklerine göre istatistiksel olarak anlamlı bir farklılık göstermediği, ancak uzaktan eğitim yarar algısının bu özelliklere göre kısmen farklılaştığı belirlenmiştir. Son olarak, yapılan korelasyon analizine göre, öğretim üyelerinin uzaktan eğitimdeki öz yeterlik algıları ile yarar algıları arasında herhangi bir ilişki olmadığı sonucuna ulaşılmıştır. Bu bulgular, uzaktan eğitimin benimsenmesi ve etkin kullanımı için öğretim üyelerinin eğitim ihtiyaçlarının ve destek mekanizmalarının yeniden gözden geçirilmesi gerektiğini ortaya koymaktadır.
ÖĞRETİM ÜYELERİNİN UZAKTAN EĞİTİM ÖZ YETERLİK VE YARAR ALGILARININ DEĞERLENDİRİLMESİ: FIRAT ÜNİVERSİTESİ İKTİSADİ VE İDARİ BİLİMLER FAKÜLTESİ ÖĞRETİM ÜYELERİ ÜZERİNE AMPİRİK BİR ÇALIŞMA
Keywords: Applied Economics (Other); Uygulamalı Ekonomi (Diğer)